1995
DOI: 10.1111/j.1440-1835.1995.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

An immunofluorescence study on lectin binding sites in gametes of Ectocarpus siliculosus (Ectocarpales, Phaeophyceae)

Abstract: SUMMARY The distribution of binding sites for the lectins WGA, DSA. RCA I, PNA, AAA, MAA. SNA, GNA. and Con A in gametes of both sexes of the brown alga, Ectocarpus siliculosus (Dillw.) Lyngbye, was investigated by fluorescence microscopy. Digoxigenin‐conjugated lectins and an FITC‐anti‐digoxigenin antibody were used as a high sensitivity detection system. Organelles and other distinct cellular domains could be distinguished by their binding specificities. Glycoconjugates associated with one flagellum were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Gamete fusion in Ectocarpus follows a stepwise process that begins with the attraction of male gametes to the pheromone ectocarpene produced by settled female gametes ( 47 ) and then proceeds with gamete recognition and cell-cell fusion ( 48 , 49 ). We examined the mating behavior of the apt and hmg1, hmg2, and hmg3 mutant lines in response to female gametes, using high-speed video microscopy.…”
Section: Hmg-sex Is Required For Male Gamete Productionmentioning
confidence: 99%
“…Gamete fusion in Ectocarpus follows a stepwise process that begins with the attraction of male gametes to the pheromone ectocarpene produced by settled female gametes ( 47 ) and then proceeds with gamete recognition and cell-cell fusion ( 48 , 49 ). We examined the mating behavior of the apt and hmg1, hmg2, and hmg3 mutant lines in response to female gametes, using high-speed video microscopy.…”
Section: Hmg-sex Is Required For Male Gamete Productionmentioning
confidence: 99%
“…There is evidence that cell‐to‐cell recognition between Ectocarpus gametes is mediated by N‐acetyl glucosamine residues exposed on the plasma membrane of the female gametes and that these residues are specifically recognized by a receptor on the male gamete (Schmid, 1993; Schmid et al ., 1994a). In addition, the lectins concanavalin A (Con A) and Aleuria aurantia agglutinin (AAA) bind specifically to the anterior flagella of Ectocarpus gametes and the molecules with which they interact also may be involved in the gamete recognition process (Maier & Schmid, 1995).…”
Section: Developmentmentioning
confidence: 99%
“…Figure 2, a and b, shows that FITC‐ConA strongly bound to the mastigonemes on both sides of the anterior flagellum in O. danica , whereas no fluorescence was detected on the posterior flagella, as in gametes of Ectocarpus (Maier and Schmid 1995). The cell body of O. danica was also strongly labeled by FITC‐ConA, showing that the cell body may contain many N‐linked glycoproteins.…”
Section: Resultsmentioning
confidence: 99%
“…Chen and Haines (1976), based on the results of periodic acid‐Schiff staining, demonstrated that the mastigoneme proteins of O. danica are glycoproteins. Maier and Schmid (1995) reported that some kinds of lectin (ConA: Canavalia ensiformis agglutinin; AAA: Aleuria aurantia agglutinin), carbohydrate‐binding proteins with high specificity and affinity, bind to mastigonemes on the anterior flagellum of the gametes of Ectocarpus siliculosus (Dillwyn) Lyngb (Phaeophyceae). In our experiment, ConA also bound to the mastigomenes of O. danica .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation